2015
DOI: 10.1007/s00464-015-4278-7
|View full text |Cite
|
Sign up to set email alerts
|

Face and construct validation of a next generation virtual reality (Gen2-VR©) surgical simulator

Abstract: Introduction Surgical performance is affected by distractors and interruptions to surgical workflow that exist in the operating room. However, traditional surgical simulators are used to train surgeons in a skills lab that does not recreate these conditions. To overcome this limitation, we have developed a novel, immersive virtual reality (Gen2-VR©) system to train surgeons in these environments. This study was to establish face and construct validity of our system. Methods and Procedures The study was a wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Regarding sample size, the average number of participants was 39.69 (min = 10, max = 148, SD= 37.33). Looking more closely at their study design, 17 studies used an experimental design (pre-test/post-test, group comparisons or control/test group comparisons) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) , nine were observational studies (18)(19)(20)(45)(46)(47)(48)(49)(50) , and one was based on qualitative interviews (51) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding sample size, the average number of participants was 39.69 (min = 10, max = 148, SD= 37.33). Looking more closely at their study design, 17 studies used an experimental design (pre-test/post-test, group comparisons or control/test group comparisons) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) , nine were observational studies (18)(19)(20)(45)(46)(47)(48)(49)(50) , and one was based on qualitative interviews (51) .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the studies include a range of professions: nurses feature in eight articles (19,20,32,37,38,40,48,49) , surgeons (33,35,38,39,43,45,46) in seven, and five articles mention other professionals (18,19,32,37,38) . With regard to students, 12 articles involve residents or postgraduate trainees (18,33,35,36,(38)(39)(40)42,(44)(45)(46)48) , ten concern health students regardless of their level or specialty (30,31,39,41,(44)(45)(46)(47)50,51) , and three articles mention trainees (29,34,38) .…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collecting participant feedback regarding face validity is a commonly used approach in the field of surgical simulation. In this context, the opinions of expert surgeons are often sought about how the simulation looks and feels and is an important part of simulation validation (Sankaranarayanan et al, 2016;Roberts et al, 2017). A similar approach is also used in the development and testing of aircraft simulations with expert pilots (Perfect et al, 2014).…”
Section: Face Validitymentioning
confidence: 99%
“…Moreover, observation of experts during the task analysis showed that they usually keep the same head position when manipulating the needle. Finally, a recent study has shown that head tracking can disturb the users when performing a surgical task on a virtual simulator [29]. This led to the design decision to setup a fixed point of view for the user, i.e.…”
Section: Figure 6: Evaluation Of the Interaction Pointmentioning
confidence: 99%